POLITIK HUKUM LARANGAN ANGGOTA BADAN PERMUSYWARATAN DESA SEBAGAI PENGURUS PARTAI POLITIK BERDASARKAN UNDANG-UNDANGNOMOR 6 TAHUN 2014 TENTANG DESA - M. Agum Wira Yudha Gumelar; Junaidi Junaidi; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In article 67 number 8 of Law Number 6 of 2014 concerning Villages it isexplained that the Village Consultative Body is prohibited from "becoming theadministrator of a political party". Cases of multiple positions are quitecommonplace in the nation and state, but their existence cannot be fully acceptedand they are even more likely to be rejected due to many factors, for example,they can cause conflicts of interest, the occurrence of multiple incomes, weaksupervision and so on.This type of research can be classified in the type of Normative legalresearch, which reveals legislation relating to legal theories that are the object ofresearch. The approach taken uses a qualitative analysis approach by looking fordata both in books, journals and other scientific works related to this research.The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the research results are First,the political law prohibiting members of the Village Consultative Council aspolitical party administrators based on Law Number 6 of 2014 concerningVillages and the impact or implications where the political law prohibitioncreates village regulations that are oriented to the function of protecting andchanneling the aspirations of the village community, the supervisory functionsupervises the performance of the village headOf course, this article still createsmisinterpretation, therefore the Village Consultative Body cannot hold concurrentpositions as administrators of political parties, especially political parties fundedby the APBN and APBD. The prohibition of concurrent positions on the VillageConsultative Council in political parties in Law Number 2 of 2008 concerningPolitical Parties also contains no provisions that specifically regulate theprohibition of concurrent positions as political party administrators. Thelegislation also does not explain the concept of multiple positions clearly.Keywords: Village Consultative Body, Political Parties, Legal Politics,Prohibition, Ideal Ideas.